Solusi damai Islam Kristen di Indonesia - Husaini, Adian, 1965- ([Jakarta] : Pustaka Da'i, 2003)
Interreligious peace solution between Islam and Christian in Indonesia
Buku rujukan : p. 221-224
Keywords: Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Islam -- Indonesia